Barbarians at the Gatekeepers?: A Proposal for a Modified Strict Liability Regime - Frank Partnoy (Washington University Law Quarterly, 2001)
This Article fills a few of the gaps in current scholarship about gatekeepers and sets forth a proposal for a modified strict liability regime that would avoid many of the problems and costs associated with the current due diligence-based approaches. Under the proposed regime, gatekeepers would be strictly liable for any securities fraud damages paid by the issuer pursuant to a settlement or judgment. Gatekeepers would not have any due diligence based defenses for securities fraud. Instead, gatekeepers could limit their liability by agreeing to and disclosing a percentage limitation on the scope of their liability for the issuer’s damages.
Keywords: Lawyers – Malpractice; Accountants – Malpractice; Strict liability; Moody& #x27; s Investors Service Inc.; Underwriters Laboratories Inc.; Accounting services; Investment banks; Securities fraud; Securities Act of 1933